2021
DOI: 10.3390/plants10050910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Climate Change Variables on the Ecology and Management of Sesbania cannabina through Glyphosate

Abstract: An elevated atmospheric carbon dioxide (CO2) concentration and frequent droughts are two anticipated climate change scenarios in which certain invasive weeds may develop competitive advantages over crops and adversely impact productivity and herbicide efficacy. Hence, a study was conducted to explore the effect of different climatic scenarios on the growth and management of Sesbania cannabina (Retz.) Pers with glyphosate. The variables investigated were two CO2 concentrations (400 and 700 ppm), two soil moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Most of the previous simulation studies report a reduced efficacy of herbicides under high CO 2 concentration [25][26][27]. At the same time, a neutral effect of elevated CO 2 concentration on herbicide efficacy against weeds has also been reported in rare cases [25,[28][29][30]. Jabran and Do gan [28] showed that the activity of glyphosate was not impacted despite the positively stimulated weed growth at 450 ppm CO 2 treatment.…”
Section: Application Of Pesticides In Agriculturementioning
confidence: 95%
See 1 more Smart Citation
“…Most of the previous simulation studies report a reduced efficacy of herbicides under high CO 2 concentration [25][26][27]. At the same time, a neutral effect of elevated CO 2 concentration on herbicide efficacy against weeds has also been reported in rare cases [25,[28][29][30]. Jabran and Do gan [28] showed that the activity of glyphosate was not impacted despite the positively stimulated weed growth at 450 ppm CO 2 treatment.…”
Section: Application Of Pesticides In Agriculturementioning
confidence: 95%
“…The overall efficacy of glyphosate was not significantly impacted at the end of the 21 days of their observation period. The recommended dosage of glyphosate application (1034 g ae ha −1 ) gave 100% biomass reduction under ambient and elevated CO 2 environments for S. cannabina weed [30]. On the other hand, in the experiment testing on an extensive range of weeds (vine, herb, shrub and grass species) under elevated atmospheric CO 2 concentration (550 ppm), weed species demonstrated different responses and tolerance levels towards glyphosate application [25].…”
Section: Application Of Pesticides In Agriculturementioning
confidence: 97%